Métodos de avaliação da eficácia dos tratamentos para a dor - Barros, Guilherme Antonio Moreira de [UNESP] (Prous Science, 2009)
Pain is a subjective condition and, thus, difficult to measure. The best tools to assess pain are the pain evaluation questionnaires, which provide either diagnostic, pain evolution or pain intensity information. To provide information which could help differentiate between nociceptive pain and neuropathic pain is one of the most important functions of these questionnaires. The questionnaires can measure pain intensity, quality of life, or sleep quality. Quality of life and sleep are two really important characteristics to assess the pain impact on patients' life. Pain intensity assessing questionnaires combine physical evaluations with questions, providing information either from the patient sensations or clinical assessment of pain manifestations as well as the underlying biological mechanisms (such as hyperalgesia or allodynia). For example, the Pain Detect questionnaire has two parts: the patient form (intuitive, with pictures and easy understandable) and the physician form. Thus, in this questionnaire, subjective information is provided by the patient and the objective one is provided by the physician. Other pain intensity questionnaires are NPSI, DN4, LANSS or StEP. Quality of life questionnaires are versatile (can be used in different pathologies). These questionnaires include functional self-evaluation questions, and other ones associated to physical and mental health. Two of such quality of life questionnaires are SF-36 and NHP. Sleep evaluation questionnaires include quantitative features such as the number of sleep interruptions, sleep latency or sleep duration as well as qualitative characteristics such as rest sensation, mood and dreams. One of the most used sleep evaluation questionnaires is PSQI, which includes patient questions and bed-partner questions, providing information from two points of view.

A dor é uma condição subjetiva, portanto, difícil de mensurar. As melhores ferramentas para avaliar a dor são os questionários de avaliação da dor, que fornecem informação diagnóstica, de evolução ou de intensidade da dor. Uma das mais importantes funções desses questionários é fornecer informações que possam ajudar a diferenciar entre dor nociceptiva e neuropática. Os questionários podem mensurar a intensidade da dor, a qualidade de vida e a qualidade do sono. As qualidades de vida e sono são 2 características importantes para avaliar o impacto da dor na vida do paciente. Os questionários de avaliação de intensidade da dor combinam avaliações físicas com perguntas, fornecendo informações baseadas nas sensações do paciente e na avaliação clínica das manifestações da dor, bem como os mecanismos biológicos subjacentes (como hiperalgesia ou alodinia). O questionário “Pain Detect” (Detector da Dor), por exemplo, consiste de 2 partes: o formulário a ser preenchido pelo paciente (intuitivo, com figuras e de fácil compreensão) e outro para ser preenchido pelo médico. Assim, a informação subjetiva é fornecida pelo paciente e a objetiva pelo medico. Outros questionários de avaliação da intensidade da dor são NPSI (Neuropathic Pain Symptom Inventory = Levantamento dos Sintomas de Dor Neuropática), DN4 (Douleur Neuropathique = Dor Neuropática), LANSS (Leeds Assessment of Neuropathic Symptoms and Signs = Avaliação de Leeds dos Sintomas e Sinais Neuropáticos) e o StEP (Standardized Evaluation of Pain = Avaliação Padronizada da Dor). Os questionários sobre a qualidade de vida são versáteis, pois podem ser usados em diferentes patologias. Eles incluem perguntas funcionais sobre auto-avaliação e outras associadas à saúde física e mental. O SF-36 (Short Form 36 = Questionário Curto com 36 perguntas) e o NHP (Nottingham Health Profile = Perfil de Saúde de Nottingham) são alguns desses questionários. Os questionários que avaliam a qualidade do sono incluem questões quantitativas, como o número de interrupções do sono, latência do sono ou duração do sono, bem como qualitativas, como sensação de descanso, humor e sonhos. Um dos questionários mais usados para avaliar o sono é o PSQI (Pittsburgh Sleep Quality Index = Índice de Pittsburgh da Qualidade do Sono), que inclui perguntas ao paciente e ao(à) seu(sua) parceiro(a) de cama e, portanto, fornece informações de dois pontos de vista.
Methods of evaluation of the effectiveness of the treatments for pain